Malaysian fruit bats phylogeny inferred using Ribosomal RNA - Japning, Jeffrine Rovie Ryan; Kho, Andy Han Guan; Kumaran, Jayaraj V.; Esa, Yuzine; Awang Husaini, Awang Ahmad Sallehin; Abdullah, Mohd Tajuddin (Universiti Putra Malaysia Press, 2008)
Fourteen species of the Malaysian fruit bats (Pteropodidae) were used in this DNA taxonomy using 1,334bp of the 12S ribosomal RNA (rRNA), transfer RNA (tRNA) valine and 16S rRNA gene segments. Previous studies using DNA found contradictions between morphology and molecular data in inferring the phylogeny of the fruit bats proposed by Andersen (1912). Our phylogenetic analysis using the neighbor-joining and the maximum parsimony methods did not support the monophyly of the subfamily Macroglossinae and the cynopterine group of the subfamily Pteropodinae as proposed by classical taxonomists. This is congruent with previous molecular studies. Here, we provide the first registered 12S rRNA, tRNA valine and 16S rRNA sequence records for Dyacopterus spadiceus in the GenBank database. This study represents the first attempt to infer the phylogenetic relationship of fruit bats from Malaysia using molecular methods.